Relationship between the A(8002)G intronic polymorphism of pre-pro-endothelin-1 gene and the endothelin-1 concentration among Tunisian coronary patients. Issue 1 (December 2015) - Chalghoum, Abdelkader; Noichri, Yosri; Dandana, Azza; Azaiez, Sana; Baudin, Bruno; Jeridi, Gouider; Miled, Abdelhédi; Ferchichi, Salima
Abstract Background Acute coronary syndromes (ACS) are complex and polygenic diseases which are a real problem of public health. These syndromes require multidisciplinary studies to understand the pathogenesis mechanisms. Our study aims to evaluate the endothelin-1 (ET-1) serum concentration in Tunisian coronary compared to controls healthy, as well as the study of the impact of an intronic polymorphism A (8002) G of pre-pro-endothelin-1 Gene (inactive precursor of ET-1) on the change in serum endothelin-1 and in the susceptibility to Acute coronary syndrome (SCA). Methods Our samples were subdivided into coronary patients (157) and healthy subjects (142). The quantification of the ET-1 concentration was performed by high performance liquid chromatography, the identification of the different genotypes of the polymorphism A(8002)G was made by PCR-RFLP. The association between the ET-1 concentration and identified genotypes was realized by adapted software for descriptive statistics, Statistical Package for the Sociological Sciences (SPSS v 21.0). Results Our study showed that the concentration of ET-1 was significantly higher in patients compared to controls and that the mutated allele prevails in patients F (G) = 0.78 and there is a minority in controls F (G) = 0.3. Secondly the homozygous genotype GG is associated with higher concentrations of ET-1 in patients and controls, heterozygous genotype AG is associated with intermediaries' values and AA genotype is related to lower values. Conclusion Although the polymorphism studied is an intronic polymorphism, it is involved in the change in serum concentration of ET-1 and is a candidate gene in susceptibility to SCA. Cardiovascular diseases are "polygenic" pathology and do not obey of the law for transmission of Mendel.